Metode Dakwah dalam Upaya Penanaman Kesadaran terhadap Kaum Blater - Rosyidi, Rosyidi (Proceedings of International Conference on Da'wa and Communication, 2019)
Da’wa has a very important role in the community, by using various methods of da’wa, it will have a significant impact in changing the society condition, thesuitability of dakwah’s methode in changing the blater’s life is very important to note, because for them it is not easy to raise awareness of they mistakes he has made during they life, so with certain methods, they will have awaraness and no longer, do not repeat they mistake that have become they habit before, the Blater have the power either physically or magical science contained in their soul, and they have inner power and they can easily gather many followers, which tends to lead to the negative actions because of that his awareness needs to be built through certain methods of da’wa. The preachers or the missionary have a very important role to change the state of a society, and a considerable become they responsibility. They can choose the method that suits according to the the object (mad'u) of the da’wa itself, because the right methods will determine the outcome or changing in the target.